Frailty and poor physical functioning as risk factors for driving cessation - Mielenz, Thelma J.; Jia, Haomiao; DiGuiseppi, Carolyn G.; Strogatz, David; Andrews, Howard F.; Molnar, Lisa J.; Eby, David W.; Hill, Linda L.; Li, Guohua (Frontiers in Public Health, 2024)
Introduction: Frailty and low physical performance are modifiable factors and thus targets for interventions to delay driving cessation (DC). The objective was to determine the impact of frailty and physical performance with DC. Methods: Multisite prospective cohort of older drivers. Key inclusion criteria: active driver age 65-79 years, valid driver’s license, cognitive impairment not significant, and the car a 1996 or newer model. Of 2990 enrolled participants, 2986 (99.9%) participants had at least one frailty or SPPB measure and are included in this study. The participants were 42% age 65-69, 86% non-Hispanic white, 53% female, 63% married and 41% with a high degree of education. The Fried Frailty Phenotype and the National Health and Aging Trends Study Expanded Short Physical Performance Battery (SPPB) were utilized. At each annual visit DC was assessed by the participant notifying the study team or self-report after no driving activity for at least 30 days via GPS. Cox proportional hazard models including time-varying covariates examined the impact of the SPPB and frailty scores with time to DC including assessment for interaction by sex. Results: Seventy-three participants (2.4%) stopped driving by the end of Year five. Among females with a fair SPPB score, the adjusted hazard ratio (HR) of DC was 0.26 (95% confidence interval (CI) 0.10 -0.65) relative to those with a poor SPPB score. For those with a good SPPB score, the adjusted HR of DC had a p-value of < 0.001. Among males with a fair SPPB score, the adjusted hazard ratio (HR) of DC was 0.45 (95% CI 0.25 -0.81) relative to those with a poor SPPB score. For males with a good SPPB score, the adjusted HR of DC was 0.19 (95% CI 0.10 -0.36). Sex was not a effect modifier between frailty and DC. For those who were categorized pre-frail or frail, the adjusted HR to DC was 6.1 (95% CI 2.7 -13.8) relative to those who were not frail. Conclusions and Relevance: Frailty and poor physical functioning are major risk factors for driving cessation. Staying physically active may help older adults to extend their driving life expectancy and mobility.